PI3K mutations in breast cancer: prognostic and therapeutic implications - Mukohara T (Dove Medical Press, 2015)
Toru MukoharaCancer Center and Division of Medical Oncology/Hematology, Kobe University Hospital, Kobe, JapanAbstract: The PI3K pathway is the most frequently enhanced oncogenic pathway in breast cancer. Among mechanisms of PI3K enhancement, PIK3CA mutations are most frequently (~30%) observed, along with protein loss of PTEN. Since the first discovery of PIK3CA mutations in solid malignancies in 2004, numerous studies have revealed the prognostic and therapeutic implications of these mutations. Although many issues remain unconfirmed, some have been carved in stone by the level of consistency they have shown among studies: 1) PIK3CA mutations are most likely to be observed in ER-positive/HER2-negative tumors, and are associated with other good prognostic characters; 2) PIK3CA mutations can coexist with other PI3K-enhancing mechanisms, such as HER2 amplification and PTEN protein loss; 3) PIK3CA mutations are potentially a good prognostic marker; 4) PIK3CA may predict a poorer tumor response to trastuzumab-based therapies, but its impact on disease-free survival and overall survival is uncertain; and 5) based on reports of early clinical trials, PIK3CA mutations do not guarantee a dramatic response to PI3K inhibitors. Collectively, there is currently no sufficient evidence to recommend routine genotyping of PIK3CA in clinical practice. Given that PIK3CA-mutant breast cancer appears to have a distinct tumor biology, development of more individualized targeted therapies based on the PIK3CA genotype is awaited.Keywords: PI3K, PIK3CA, prognostic factor, predictive factor, trastuzumab